Деякі аспекти інформатизації податкової служби України - Трофименко, Олена Григорівна; Трофименко, Елена Григорьевна; Trofimenko, Elena; Логінова, Наталія Іванівна; Логинова, Наталья Ивановна; Loginova, Natal'ja (My University, 2012)
In article examines the current status of informatization of Tax Service of Ukraine. Priority directions of the informatics of tax service were defined at present. The analysis of the possibility of using experience of different country European Union’s by the informatization of taxpayers in our country.
Трофіменко О. Г., Логінова Н. І. Деякі аспекти інформатизації податкової служби України / О. Г. Трофименко, Н. І. Логінова // Актуальні проблеми держави і права : зб. наук. пр. /редкол.: С. В. Ківалов (голов. ред.), В. М. Дрьомін (заст. голов. ред.), Ю .П. Аленін [та ін.] ;МОНмолодьспорт України, НУ «ОЮА». – Одеса : Юрид. л-ра, 2012. – Вип. 65. – С. 379-384.
Keywords: інформатизація; інформаційні технології; податкова служба; електронна форма; платники податків; информатизация; информационные технологии; налоговая служба; электронная форма; плательщики налогов; informatization; information technologies; tax service; electronic form; taxpayers